Microstructure and mechanical properties of laser melting deposited Ti2Ni3Si/NiTi Laves alloys - 董李欣 王华明 (Transactions of Nonferrous Metals Society of China, 2007)
Two Ti2Ni3Si/NiTi Laves phase alloys with chemical compositions ofNi-39Ti-11Si and Ni-42Ti-8Si （%, mole fraction, the same below）, respectively, were fabricated by the laser melting deposition manufacturing process, aiming at studying the effect of Ti, Si contents on microstructure and mechanical properties of the alloys. The Ni-39Ti-llSi alloy consisting of Ti2Ni3Si primary dendrites and Ti2Ni3Si/NiTi eutectic matrix is a conventional hypereutectic Laves phase alloy while the Ni-42Ti-8Si alloy being made up of NiTi primary dendrites uniformly distributed in Ti2Ni3Si/NiTi eutectic is a new hypoeutectic alloy. Mechanical properties of the alloys were investigated by nano-indentation test. The results show that the decrease of Si and the increase of Ti contents change the microstructures of the alloys from hypereutectic to hypoeutectic, which influences the mechanical properties of the alloys remarkably. Corrosion behaviors of the alloys were also evaluated by potentiodynamic anodic polarization curves.